The influence of climate on the effectiveness of low impact development: A systematic review. (15th April 2019) - Sohn, Wonmin; Kim, Jun-Hyun; Li, Ming-Han; Brown, Robert
Abstract: Low impact development (LID) has been increasingly practiced since its emergence in the 1990s. Although the hydrological benefits of LIDs have been extensively documented, the climate impact on LID performance remains unclear with increasing variations in spatial and temporal climate patterns. This systematic review contributes to providing a structured summary of research on how LID systems are sensitive to climate variability by empirical and hypothetical research approaches. The selected 46 peer-reviewed journal articles published between 2003 and 2017 were analyzed by key variables, including climatic factors, LID types, and hydrologic measures used to quantify LID performance. A conceptual framework formulated in this study synthesizes the relationship between climate and LID effectiveness. The results of weighted meta-analysis reveal a greater sensitivity of runoff volume to changing storm frequency than peak discharge rates, while the capacity of LID systems to reduce both volume and peak discharge rates diminishes with increasing storm intensity. Future explorations of the sensitivity of LIDs to climate fluctuations will help strategize LID installation for targeted storm patterns and flood mitigation goals. To enhance existing methods and make a balance between empirical and hypothetical knowledge, this study suggests future directions of research and encourages development of effective stormwater management policy. Highlights: LIDs performed better with a storm of lower intensity and shorter duration. LIDs in warm seasons generally outperformed those in cold seasons. A reduction in runoff volume is more subject to climate variability than peak flow. The sensitivity of LID systems to temperature changes was seldom studied. Studies of future climate impacts on LID performance increased dramatically.